MANAGEMENT OF FIQH LEARNING IN SCHOOL AN MADRASAH FOR ISLAMIC RELIGIOUS EDUCATION TEACHER - Firman Mansir (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The aim of this study examines the importance of Islamic Religious Education (PAI) teachers in managing classroom learning, especially fiqh learning in schools and madrasah. Research method used is literature study. Method of literature study is method of collecting some data obtained through notes, works, or pictures. Thus, discussion or data obtained are the result of exploration from several relevant reading sources. This is an effort, action and method taken by Islamic Religious Education teachers in realizing dynamic and interesting fiqh learning. The management of fiqh learning is very important. Thus, there are no mistakes in understanding fiqh materials which are full of Ulama/theologians’ thoughts, views of mazhab and good and correct worship procedures. Therefore, a fiqh learning approach in schools and madrasa needs to be present using a contextual approach that relates to the context of daily life. One way to make this happen was by using various methods, such as lecture method, the question and answer method, the based method, the recitation method and the drill method. The results explain that the management of fiqh learning in schools and madrasahs consists of lesson planning, learning implementation and learning evaluation. AbstrakPenelitian ini bertujuan menjelaskan tentang pentingnya guru Pendidikan Agama Islam (PAI) dalam mengatur sebuah pembelajaran di kelas khususnya pembelajaran fiqh di sekolah dan Madrasah. Metode penelitian yang digunakan adalah studi pustaka, metode ini dilakukan dengan cara pengumpulan data melalui catatan, karya atau gambar, dengan begitu pembahasan atau data yang diperoleh merupakan hasil eksplorasi dari beberapa sumber bacaan yang relevan. Hasil penelitian menunjukkan bahwa berbagai usaha, tindakan serta cara yang dilakukan oleh guru PAI dalam mewujudkan pembelajaran fiqh yang dinamis, menarik dan tidak membosankan. Manajemen pembelajaran fiqh sangat penting agar tidak terjadi kesalahan dalam memahami materi-materi fiqh yang sarat dengan pemikiran-pemikiran ulama, perbedaan pandangan mazhab serta tata cara ibadah yang baik dan benar. Karena itu, sebuah pendekatan pembelajaran fiqh disekolah dan madrasah perlu hadir dengan menggunakan pendekatan kontekstual yang mengaitkan pada konteks kehidupan sehari-hari. Salah satu cara mewujudkan hal di atas dengan menggunakan berbagai metode, yang terdiri dari metode ceramah, metode tanya jawab, metode demonstrasi, metode resitasi dan metode drill. Hasilnya kemudian menjelaskan bahwa manajemen pembelajaran fiqh yang ada di sekolah dan madrasah terdiri dari perencanaan pembelajaran, pelaksanaan pembelajaran dan evaluasi pembelajaran.